Defective germinal center selection results in persistence of self-reactive B cells from the primary to the secondary repertoire in Primary Antiphospholipid Syndrome - Dieudonné, Yannick; Lorenzetti, Raquel; Rottura, Julien; Janowska, Iga; Frenger, Quentin; Jacquel, Léa; Vollmer, Olivier; Carbone, Francesco; Chengsong, Zhu; Luka, Marine; Depauw, Sabine; Wadier, Nadège; et al. (Nature communications, 2024)
Primary antiphospholipid syndrome (PAPS) is a life-threatening clotting disorder mediated by pathogenic autoantibodies. Here we dissect the origin of self-reactive B cells in human PAPS using peripheral blood and bone marrow of patients with triple-positive PAPS via combined single-cell RNA sequencing, B cell receptors (BCR) repertoire profiling, CITEseq analysis and single cell immortalization. We find that antiphospholipid (aPL)-specific B cells are present in the naive compartment, polyreactive, and derived from the natural repertoire. Furthermore, B cells with aPL specificities are not eliminated in patients with PAPS, persist until the memory and long-lived plasma cell stages, likely after defective germinal center selection, while becoming less polyreactive. Lastly, compared with the non-PAPS cells, PAPS B cells exhibit distinct IFN and APRIL signature as well as dysregulated mTORC1 and MYC pathways. Our findings may thus elucidate the survival mechanisms of these autoreactive B cells and suggest potential therapeutic targets for the treatment of PAPS. Primary antiphospholipid syndrome (PAPS) is a clotting disorder attributed to autoreactive antibodies produced by B cells. Here the authors show, using single cell omics and B cell repertoire data, that autoreactive B cells originate from the natural B cell repertoire and escape germinal center selection to persist in PAPS patient via potential dysregulation of mTORC1 and MYC pathways.